The state makes migration—and migration makes the state? - Lorenzo Ghione (L’Année du Maghreb)
This paper explores the relationship between migration politics and authoritarian regime consolidation in Tunisia, focusing on the period following President Kaïs Saïed’s coup in 2021. The study contributes to the growing literature on migration and state-building by showing how migration politics shapes and is shaped by authoritarian regimes. Borrowing from Gerschewski’s framework of autocratic stabilisation, the study identifies three components related to migration politics underpinning autocratic stabilisation: financial resources, legitimation, and repression. Through a securitised and politicised migration management, the Tunisian regime has secured substantial financial support from Europe while portraying immigrants as domestic threats has legitimised its increasingly autocratic policies. Repression, manifested in migrants’ deportations and crackdowns on civil society organisations, has further enhanced state control. This research draws on extensive fieldwork, including interviews and desk-based analysis, to highlight how migration politics has supported Kaïs Saïed’s authoritarian nation-building project. The paper also calls for further reflection on the implications of external support for authoritarian practices and underlines the transformative power of migration politics in relation to state structures.